LEADERSHIP AND BUSINESS ENTREPRENEURSHIP: A BIBLIOMETRIC ANALYSIS - Wilder Quintero-Quintero; Sir-Alexci Suarez Castrillon (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This research aimed to develop a bibliometric analysis on leadership and entrepreneurship, using the Scopus database from 2000 to 2022. For this purpose, a descriptive methodology with a qualitative approach was used, where the historical development of the publications was analysed using Excel software to collect and analyse the information. As for the results, the scientific production represented in the volume of publications made, the co-occurrence of keywords through the VOSvierw software, and the most representative countries where the largest number of publications have been made in this topic of study were analysed, in addition, the most important studies were evaluated according to the citation index and a discussion is made regarding the comparison with other similar studies. Finally, the study concludes that corporate leadership and entrepreneurship has been widely studied, especially since 2014, which represents 70% of the publications of the last 20 years.